2021
DOI: 10.1101/2021.09.21.21262899
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Imaging Sensitive and Drug-Resistant Bacterial Infection with [11C]-TMP: In Vitro and First-in-Human Evaluation

Abstract: Recently, several molecular imaging strategies have developed to image bacterial infections in humans. Nuclear approaches, specifically positron emission tomography (PET), affords sensitive detection and the ability to non-invasively locate infections deep within the body. Two key radiotracer classes have arisen: metabolic approaches targeting bacterial specific biochemical transformations, and antibiotic-based approaches that have inherent selectivity for bacteria over mammalian cells. A critical question for… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…Given how ubiquitous and conserved this pathway is among different bacteria, the incorporation of PABA into tetrahydrofolate by the bacterial dihydropteroate synthase has been considered as a promising target for pathogen-specific imaging. Inhibitors with nanomolar affinity to key enzymes within the folate synthesis pathway, such as radiolabeled trimethoprim ( 11 C-TMP) and its analog fluoropropyl-trimethoprim ( 18 F-FPTMP), have also been evaluated as bacteria-specific imaging agents ( 18 , 19 ). PABA and its antibacterial structural analog, sulfonamide, enter bacterial cells by passive diffusion across the cell membrane ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given how ubiquitous and conserved this pathway is among different bacteria, the incorporation of PABA into tetrahydrofolate by the bacterial dihydropteroate synthase has been considered as a promising target for pathogen-specific imaging. Inhibitors with nanomolar affinity to key enzymes within the folate synthesis pathway, such as radiolabeled trimethoprim ( 11 C-TMP) and its analog fluoropropyl-trimethoprim ( 18 F-FPTMP), have also been evaluated as bacteria-specific imaging agents ( 18 , 19 ). PABA and its antibacterial structural analog, sulfonamide, enter bacterial cells by passive diffusion across the cell membrane ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this wildtype DHFR copy in TMP-resistant strains is responsible for the sustained, high levels of intracellular [ 11 C]TMP. [20] The biodistribution of [ 11 C]TMP-PET in healthy human subjects [19] and a proof-of-concept study in patients with known or suspected bacterial infections [20] showed hepatic tracer accumulation and activity in kidneys and bladderrepresenting TMP metabolism and excretion. A patient with biopsy-proven methicillin-sensitive S. aureus (MSSA) discitis, scanned with [ 11 C]TMP, showed asymmetric uptake in the left L4-5 facet that resolved completely on the follow-up scan.…”
Section: [ 11 C]trimethoprim ([ 11 C]tmp)mentioning
confidence: 99%
“…[17] Hence, Sell- 18 F]fluoropropyl-trimethoprim and evaluated their potential as bacterial-specific imaging agents. [18][19][20]…”
Section: Antibiotics As Pet Imaging Agents 21 Antifolates (Trimethoprim)mentioning
confidence: 99%
“…A dot blot assay with various concentrations of E. coli DHFR incubated with [ 11 C]TMP showed a concentration‐dependent, specific radiotracer binding [21] . To assess bacterial [ 11 C]TMP uptake and determine if antibiotic resistance may affect radiotracer uptake levels, extensive in vitro uptake studies were performed across a panel of wild‐type‐ and TMP‐resistant bacterial strains expressing mutant DHFR enzymes [20] . In all cases, both drug‐susceptible and ‐resistant bacterial strains showed similar and sustained [ 11 C]TMP uptake compared to negative controls (either DHFR knockout strain, heat‐killed, or TMP‐blocked bacteria).…”
Section: Antibiotics As Pet Imaging Agentsmentioning
confidence: 99%
See 1 more Smart Citation